The relationship between regional development, smart mobility and transportation planning: a bibliometric analysis - Almassawa, Syafieq Fahlevi; Rustiadi, Ernan; Fauzi, Akhmad; Sutriadi, Ridwan (Frontiers in Sustainable Cities, 2025)
This paper presents a bibliometric analysis of publications from the Scopus database on regional development, smart cities, smart mobility, and transportation planning. The study retrieved 397 documents published between 2010 and 2023, utilizing keywords relevant to the research topic, and analyzed them using VOSviewer software. The findings indicate a steady increase in research output in this field since 2010. The most frequently used terms identified in this study include the main keywords: sustainability, regional planning, and smart transportation. It is recommended that “Regional Development” and “Transportation Planning” serve as primary target journals for disseminating the results of this research analysis, as they may eventually supersede previous dominant themes. Additionally, the findings suggest that researchers from countries with lower contributions to this field should explore these topics further to add depth and nuance. Research linking these keywords should be expanded and replicated to enrich the existing literature.